Perfluoroalkyl substances and risk of type II diabetes: A prospective nested case-control study. (February 2019) - Donat-Vargas, Carolina; Bergdahl, Ingvar A.; Tornevi, Andreas; Wennberg, Maria; Sommar, Johan; Kiviranta, Hannu; Koponen, Jani; Rolandsson, Olov; Åkesson, Agneta
Abstract: Background: Perfluoroalkyl substances (PFAS) have drawn much attention due to bioaccumulation potential and their current omnipresence in human blood. We assessed whether plasma PFAS, suspected to induce endocrine-disrupting effects, were prospectively associated with clinical type 2 diabetes (T2D) risk. Methods: We established a nested case-control study within the Swedish prospective population-based Västerbotten Intervention Programme cohort. Several PFAS were measured in plasma from a subset of 124 case-control pairs at baseline (during 1990–2003) and at 10-year follow-up. T2D cases were matched (1:1) according to gender, age and sample date with participants without T2D (controls). Conditional logistic regressions were used to prospectively assess risk of T2D by baseline PFAS plasma concentrations. Associations between long-term PFAS plasma levels (mean of baseline and follow-up) and insulin resistance (HOMA2-IR) and beta-cell function (HOMA2-B%) at follow-up were prospectively explored among 178 and 181 controls, respectively, by multivariable linear regressions. Results: After adjusting for gender, age, sample year, diet and body mass index, the odds ratio of T2D for the sum of PFAS (Σ z-score PFAS) was 0.52 (95% confidence interval, CI: 0.20, 1.36), comparing third with first tertile; and 0.92 (95% CI: 0.84, 1.00) per one standard deviation increment of sum of log-transformed PFAS. Among the controls, the adjusted β of HOMA2-IR and HOMA-B% for the sum of PFAS were −0.26 (95% CI: −0.52, −0.01) and −9.61 (95% CI: −22.60, 3.39) respectively comparing third with first tertile. Conclusions: This prospective nested case-control study yielded overall inverse associations between individual PFAS and risk of T2D, although mostly non-significant. Among participants without T2D, long-term PFAS exposure was prospectively associated with lower insulin resistance. Highlights: PFAS have endocrine-disrupting properties, activate PPARs and may affect T2D risk We observed weak indications of PFAS-associated lower T2D risk. Long-term PFAS were inversely associated with insulin resistance in non-diabetics Confounding from dietary sources of PFAS may explain overall conflicting results Further research to tease out the true impact of PFAS in human T2D is warranted